The Influence of Transformational Leadership Style, Organizational Communication, and Career Development on Employee Performance with Job Satisfaction as an Intervening Variable - Saharso Saharso; Febrianti, Dwi (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study was to analyze the impact of transformational leadership style, organizational communication, and career development variables on employee performance at the Directorate General of Regional Development, Ministry of Home Affairs of the Republic of Indonesia through job satisfaction variables. A quantitative research study using questionnaire collection techniques and Smart-PLS SEM with 149 permanent employees as sample data. The findings showed that transformational leadership style and career development had a positive but insignificant effect on job satisfaction while organizational communication had a significant impact on job satisfaction. In addition, transformational leadership style, work communication, and career development have a significant positive effect on employee performance but not on job satisfaction. Another result was that job satisfaction could not mediate transformational leadership style and career development on employee performance, but it was able to mediate the relationship between organizational communication and employee performance. Therefore, it is recommended for management to focus on fostering effective communication channels and career development programs to improve employee performance.